(untitled) (Journal of Dhaka Medical College, 2018)
Background & objective: Perinatal asphyxia affects all organs of the body and brain is the most affected organ. The study was undertaken to find out the status of serum magnesium and calcium level and their significant association among asphyxiated term newborns with moderate to severe HIE. Material & methods: The Cross sectional study was done in the Department of Neonatology, Dhaka Medical College Hospital during January 2012 to July 2012. A total of 102 asphyxiated term neonates were enrolled , who has H/O perinatal asphyxia and had Apgar score of 6 or <6 at 5 minutes. Clinical grading of HIE into moderate and severe was done according to modified Sarnat and Sarnat scoring system .Under aseptic precautions with standard protocol , estimation of serum magnesium and calcium level in venous blood was done at 48 hours and 7th day of birth . Among the study population , 17 patients had died during follow up and 4 patients were absconded. Finally 81 patients were evaluated by both blood samples though initial 102 cases were evaluated by their first sample. 50 normal healthy infants were also evaluated for serum magnesium and calcium at their 48 hours of birth. Chi-square test was used to assess statistical significance, Pearson correlation coefficient test was done to find out correlation between serum magnesium and calcium status and APGAR score & t test was done to assess the comparison between the values of serum magnesium and calcium found on two occasions. Results: Of 102 cases majority (58%) were male. Most of the cases (65.68%) were moderate HIE. Mean serum magnesium was 1.36(0.9-2.8) mg/dl and 1.16(.88-2.6) mg/dl among HIE II and HIE III respectively (p<0.05). Mean serum calcium of HIE II and HIE III were 7.14(5.1-9.6) mg/dl and 6.58(5.3-9.0) mg/dl respectively (p<0.05). There is positive correlation with individual APGAR score with serum magnesium (r=0.229, p=0.02) and serum calcium (r=0.231, p=0.019) level. Hypocalcaemia was found 35.82% and 57.14% among HIE II And HIE III cases respectively(p<0.01). Hypomagnesaemia was found 28.36% and 45.71% among HIE II and HIE III (p<0.05). Conclusion: Hypomagnesaemia and hypocalcaemia are significantly associated with the degree of severity of HIE. J Dhaka Medical College, Vol. 26, No.2, October, 2017, Page 148-152